Epigenetic and Transcriptional Control of Erythropoiesis - Wells, Maeve; Steiner, Laurie (Frontiers in Genetics, 2022)
Erythropoiesis is a process of enormous magnitude, with the average person generating 2-3 million red cells every second. Erythroid progenitors start as large cells with large nuclei, and over the course of 3-4 cell divisions they undergo a dramatic decrease in cell size accompanied by profound nuclear condensation, which culminates in enucleation. As maturing erythroblasts are undergoing these dramatic phenotypic changes, they accumulate hemoglobin and express high levels of other erythroid-specific genes, while silencing much of the non-erythroid transcriptome. These phenotypic and gene expression changes are associated with distinct changes in the chromatin landscape, and require close coordination between transcription factors and epigenetic regulators, as well as precise regulation of RNA polymerase II activity. Disruption of these processes are associated with inherited anemias and myelodysplastic syndromes. Here, we review the epigenetic mechanisms that govern terminal erythroid maturation, and their role in human disease.